Case Report: Findings Suggestive of Paraclinical Progressive Multifocal Leukoencephalopathy and Lung Cancer-Derived Brain Metastases in an MS Patient Treated With Fingolimod - Maass, Fabian; von Gottberg, Philipp; Franz, Jonas; Stadelmann, Christine; Bähr, Mathias; Weber, Martin S. (Frontiers in Neurology, 2021)
Fingolimod represents a highly effective disease-modifying drug in patients with active relapsing-remitting multiple sclerosis (RRMS). Its immunosuppressive effects can mediate adverse events like increased risk of cancer development or appearance of opportunistic infections. Progressive multifocal leukoencephalopathy (PML)–representing a severe opportunistic infection–has been only infrequently described during Fingolimod treatment. Here, we present a case of a 63-year-old women with pre-diagnosed RRMS who presented with new multiple cerebral lesions in a routine MRI scan, also including a tumefactive lesion in the left parietal lobe, eventually leading to the diagnosis of brain metastases derived by an adenocarcinoma of the lung. Additionally, a JCV-DNA-PCR in the cerebrospinal fluid revealed positive results, corresponding to a paraclinical progressive multifocal leukoencephalopathy. In conclusion, adverse events potentially associated with immunosuppression can occur during Fingolimod treatment. In this context, the occurrence of cancer and opportunistic infections should be carefully monitored. Here, we report a case in which JCV-DNA-PCR in the cerebrospinal fluid suggests asymptomatic PML and simultaneously lung cancer brain metastases developed. While it is rather unlikely that either event occurred as an adverse event of fingolimod treatment, a contributing effect cannot be formally excluded.